Labour market dynamics in Spanish regions: Evaluating asymmetries in troublesome times - Hector Sala; Pedro Trivín (SERIEs - Journal of the Spanish Economic Association, 2014)
The Spanish labour market disproportionately booms in expansions and bursts in recessions; meanwhile, its regions' relative position persists: those with the highest unemployment rates in 1996 were also in the worse position in 2012. To examine this twofold feature, we apply Blanchard and Katz's (Brookings Pap Econ Act 1:1 - 75, 1992) methodology and evaluate how the Spanish labour market reacts to regional employment shocks in a variety of cases. Shock responses are channelled via changes in unemployment, labour market participation, and spatial mobility. Our results provide evidence of asymmetric responses across business cycle phases (1996 - 2007 and 2008 - 2012). While changes in participation rates are the main adjustment mechanism in expansion, unemployment and spatial mobility become the central ones in recession. We also provide evidence of real wage rigidities in both periods, due to rigidities in both nominal wages and consumer prices. We conclude with a cluster analysis showing that high and low unemployment regions have similar responses in the short-run while, in the long-run, the former are more reactive in terms of spatial mobility. Overall, we provide evidence that people in a region are more willing to migrate (relative to the national average) when a regional shock occurs in relatively worse economic contexts.
Keywords: J20; E24; J61; R11; 330; Employment; Unemployment; Regional labour markets; Spain